Kekkonen, Eurovision and Helsinki: NER-based Analysis on National Audiovisual Heritage - Kannisto Maiju; Kauppinen Pekka (Helsinki University Press, 2022)
The chapter focuses on the Finnish public service broadcasting company Yle (former Yleisradio), which was founded in 1926 and on the possible uses by digital historians of its online archive. The dataset used in the research are non-traditional in that it consists of Yle’s archival metadata. This digital material is analysed as a historical source material using the method of Named Entity Recognition (NER) as it is implemented in the digital tool the Finnish rule-based named-entity recogniser (FiNER). This chapter explores how a canon of salient Finnish events and persons is built up in the national audio-visual archive in the digital age. The authors suggest that the cultural contextualising and close reading of the themes pointed out by the results of NER-based analysis still play an important role in the analytical process as the metadata material, as well as the digital tool, has its limitations.
Digital Histories: Emergent Approaches within the New Digital History.